Comparison of primipara women’s pre-pregnancy, pregnancy, and postpartum sexual lives - Türk, Rukiye; Çılgın, Hasan (Journal of Surgery and Medicine, 2020)
Aim: Sexual dysfunction can affect women’s quality of life and marriage. This study compared the sexual lives of primipara women before, during pregnancy and in the postpartum period. Methods: This descriptive follow-up research comprised 100 primipara women who agreed to participate in the study. Data were collected using the survey form and the Arizona Sexual Experiences Scale. Number, percentage, means, standard deviation, median, minimum, maximum values and Friedman analysis were used to analyze the data. Results: Women’s sexual desire and orgasm level before pregnancy were significantly better than their postpartum orgasm level. Our study results showed that the level of sexual arousal and lubrication before pregnancy was significantly better than that after birth. We also determined that women’s postpartum orgasm satisfaction was significantly less than their pre-pregnancy and pregnancy orgasm satisfaction. Based on Arizona Sexual Experiences Scale average, the sexual dysfunction of women before pregnancy was significantly less than during the pregnancy and postpartum periods and the pregnancy period was better than the postpartum period (P<0.001). Conclusion: This study has reported that sexual dysfunction in women is less during pre-pregnancy; however, it increases during pregnancy and the postpartum period.